The Assemblies of God : Godly love and the revitalization of American Pentecostalism - Poloma, Margaret M.; Green, John Clifford, 1953- (New York : New York University Press, 2010)
The Assemblies of God draws on fresh, up-to-date research including quantitative surveys and interviews conducted within twenty-two Assemblies of God congregations to offer a new sociological portrait of the AG for the new millennium. The authors suggest that there is a revitalization of the movement in the works within the context of the larger Pentecostal upswing, and that this revitalization may be spurred by what the authors call "godly love" : the dynamic interaction between perceived divine and human love that enlivens and expands adherents' benevolence.
Congregational overview -- Charisma and structure in the Assemblies of God : theoretical overview -- Pentecostal identity and the charismata : mixed motivation and religious experience -- Structure and charisma : doctrine, power, and administration -- Spirit baptism and spiritual transformation : an exercise in socio-theology -- Spiritual empowerment : pray-ers, prophets, and healers in the pews -- Law of love and love of law : beliefs, mores, and faces of love -- Ushering in the kingdom of God : religious values, godly love, and public affairs -- Covenants, contracts, and godly love / with Matthew T. Lee.
Includes bibliographical references (p. 239-247) and index.
Keywords: Assemblies of God; Christian sociology -- Assemblies of God; United States -- Religious life and customs; Christian sociology -- United States